Thick epitaxial YIG films with narrow FMR linewidth - Syvorotka, I. I.; Syvorotka, I. M.; Ubizskii, S. B. (Видавництво Львівської політехніки, 2012)
The La-doped yttrium iron garnet (YIG) films with thickness up to 130 μm were grown by liquid phase epitaxy (LPE) method. All grown thick films demonstrate “mirror” and “striation” types of surface morphology that depend from film growth temperature and thickness. Addition of B2O3 is favourable to a change the surface morphology into a “mirror” one. The mechanisms of the morphological changes are discussed. It was found that the ferromagnetic resonance (FMR) linewidth appreciably depends from surface morphology of grown films. For thick films with “mirror” surface the FMR linewidth is less than 0.8 Oe and more than ten times less in comparison with films with “striation” surface.
Keywords: liquid phase epitaxy; yttrium iron garnet films; surface morphology; ferromagnetic resonance linewidth